Visualizing the Body in Art, Anatomy, and Medicine since 1800
1 online resource.
Keywords: This book expands the art historical perspective on art's connection to anatomy and medicine, bringing together in one text several case studies from various methodological perspectives. The contributors focus on the common visual and bodily nature of (figural) art, anatomy, and medicine around the central concept of modeling (posing, exemplifying and fabricating). Topics covered include the role of anatomical study in artistic training, the importance of art and visual literacy in anatomical/medical training and in the dissemination (via models) of medical knowledge/information, and artistic representations of the medical body in the contexts of public health and propaganda.